Insurmountable simplicities : 39 philosophical conundrums - Casati, Roberto, 1961- (Columbia University Press, 2006)
""Perhaps not all the stories that follow are true. They could, however, be true, and the Reader is invited to ponder this.""So begins Insurmountable Simplicities, Roberto Casati and Achille Varzi's colorful incarnation of the many philosophical conundrums that hide in the wrinkles of everyday life. Why do mirrors seem to invert left and right but not up and down? How do we know whether strawberries taste the same for everyone? Where is it written that we must observe the law, and if it is not written, why should we observe it? What if we could swap brains-or the rest of.